Optimized Node Deployment Algorithm and Parameter Investigation in a Mobile Sensor Network for Robotic Systems. (30th October 2015) - Tang, Rongxin; Nie, Chengfei; Qian, Xin; Deng, Xiaohua; Chen, Zhe; Liu, Zhiwei; Zhou, Meng; Pang, Ye; Xu, Xiaojun
Mobile sensor networks are an important part of modern robotics systems and are widely used in robotics applications. Therefore, sensor deployment is a key issue in current robotics systems research. Since it is one of the most popular deployment methods, in recent years the virtual force algorithm has been studied in detail by many scientists. In this paper, we focus on the virtual force algorithm and present a corresponding parameter investigation for mobile sensor deployment. We introduce an optimized virtual force algorithm based on the exchange force, in which a new shielding rule grounded in Delaunay triangulation is adopted. The algorithm employs a new performance metric called 'pair-correlation diversion', designed to evaluate the uniformity and topology of the sensor distribution. We also discuss the implementation of the algorithm's computation and analyse the influence of experimental parameters on the algorithm. Our results indicate that the area ratio, φs, and the exchange force constant, G, influence the final performance of the sensor deployment in terms of the coverage rate, the convergence time and topology uniformity. Using simulations, we were able to verify the effectiveness of our algorithm and we obtained an optimal region for the (φ s, G )-parameter space which, in the future, could be utilized as an aid for experiments in robotic sensor deployment.